Family life education with diverse populations - Ballard, Sharon M.; Taylor, Alan C. (Los Angeles, Calif. ; London : SAGE, 2012)
This text presents key strategies for family life educators working with diverse populations, including those based on race and ethnicity, family geographic location, and context.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Family life education; Families